Ideologi-Ideologi Politik Kontemporer : Islam dan Fundamentalisme, Sosialisme dan ... - Roger Eatwell (Editor) (Media TOR, 2003)
Ideologi-Ideologi Politik Kontemporer : Islam dan Fundamentalisme, Sosialisme dan ...